High involvement work practices often lead to burnout, but thanks to humble leadership. Issue 6 (30th September 2021) - Afshan, Gul; Kashif, Muhammad; Khanum, Firdous; Khuhro, Mansoor Ahmed; Akram, Umair
Abstract : Purpose: Based on the conservation of resources theory, this study aims to investigate high involvement work practices (HIWP) as an antecedent to burnout with a mediating role of perceived work–family (WF) imbalance. Moreover, this study examines whether humble leadership moderates the relationship between HIWP and WF imbalance. Design/methodology/approach: Using a time-lagged survey approach, data are collected from 200 employees working in the Indian services sector organizations. Findings: The findings demonstrate that HIWP has a direct negative effect on burnout and an indirect effect via WF imbalance. Also, humble leadership moderates the relationship between HIWP and WF imbalance. Originality/value: By studying the pessimistic view of HIWP in the Indian context, this study contributes to the scant studies available on its effect on burnout in collectivistic societies. Furthermore, humble leadership's moderating role in the relationship between HIWP and WF imbalance is unique to this study.